2022
DOI: 10.1371/journal.pntd.0010232
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Chagas disease in the non-endemic area of Madrid: A fifteen-year review (2004–2018)

Abstract: Background Chagas disease (CD) has become an emerging global health problem in association with the immigration of individuals from endemic areas (in LatinAmerica) to other countries.Spain is the country in Europe with the highest number of CD cases. Concerning pediatric CD, treatment is not only better tolerated by younger children but also has greater cure possibilities. The aim of this study was to describe clinical and epidemiological aspects of CD in a pediatric population diagnosed of 10 hospitals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Few series based on pediatric cases of CD in Europe have been published. The largest included 51 cases of CD in children, 50.9% of whom were born in Spain and all of whom had Latin American mothers [ 50 ]. Another study reported 45 pediatric T. cruzi cases diagnosed in Spain and Switzerland and all were children of Latin American origin.…”
Section: Pediatric Chagas Diseasementioning
confidence: 99%
See 3 more Smart Citations

Chagas Disease in Europe

Gonzalez-Sanz,
Crespillo-Andújar,
Chamorro-Tojeiro
et al. 2023
TropicalMed
“…Few series based on pediatric cases of CD in Europe have been published. The largest included 51 cases of CD in children, 50.9% of whom were born in Spain and all of whom had Latin American mothers [ 50 ]. Another study reported 45 pediatric T. cruzi cases diagnosed in Spain and Switzerland and all were children of Latin American origin.…”
Section: Pediatric Chagas Diseasementioning
confidence: 99%
“…PCR for T. cruzi was performed in 20 of the 22 cases diagnosed by serological screening and was positive in 12 cases (60%) [ 52 ]. For children born in Latin America, Bolivia was the most frequent area of origin [ 50 , 51 , 52 ].…”
Section: Pediatric Chagas Diseasementioning
confidence: 99%
See 2 more Smart Citations

Chagas Disease in Europe

Gonzalez-Sanz,
Crespillo-Andújar,
Chamorro-Tojeiro
et al. 2023
TropicalMed
“…[10] Chagas disease (CD), resulting from infection by the T. cruzi parasite, remains a significant community and individual health concern in Latin America. The WHO classifies [11] it as an NTD, highlighting the association of the disease with poverty and disadvantage, affecting communities with limited visibility and political influence. It leads to stigmatization and discrimination, receives less attention from researchers, and has a substantial impact on both illness and death rates.…”
Section: Introductionmentioning
confidence: 99%